Measurement of the Rebound Effect on Urban Household Energy Consumption Savings - Sudarmaji, Eka; Ambarwati, Sri; Munira, Mira (International Journal of Energy Economics and Policy, 2022)
This research investigated consumer behavior patterns on energy conservation and energy efficiency. We investigated the factors that influence the rebound effect based on common characteristics and Socio-economic household characteristics in urban communities. This paper also explored the conservation of electricity through the idea of "nudge." The authors used the word "encouragement" in the chosen architectural program, designed to reduce household electricity consumption so that the rebound effect did not occur in household consumption. By utilizing the 'social norms and curtailment,' households given a "nudge" can save more on their electricity consumption costs. The condition of "nudge" that we included was through information on the costs incurred by households, 'social norms and curtailment,' and energy efficiency through replacing conventional lamps with energy-efficient lamps. The research took place in urban areas in the Bantul, Jogjakarta, between December 2021 and April 2022. Sixty-two respondents divide into two groups of households, i.e., observe households (self-selected) and control households (randomly selected). Both observe and control households must have an active electricity account for at least one year and have owned a house between 50 and 200 square meters. The model used a t-paired sample through the "Non-Equivalent Groups Design" (NEGD) framework for the two comparisons. The research found that 'social norms and curtailment' can reduce household electricity consumption, has cost savings over electricity consumption on average to 16.3049% for three months, and no rebound effect on savings happened.